2010
DOI: 10.4314/gmj.v41i4.55287
|View full text |Cite
|
Sign up to set email alerts
|

A review of trabeculectomies at a Nigerian teaching Hospital

Abstract: SUMMARYBackground: Trabeculectomy is the commonest surgical procedure for glaucoma. The outcome of trabeculectomy in the treatment of all types of glaucoma over a 4-year period in a Nigerian population was reviewed. Objective: To determine the surgical rate and effectiveness of trabeculectomy in lowering of intra ocular pressure (IOP) and preservation of visual acuity. Methods: Retrospective review of all trabeculectomies (TEs) done at the Obafemi Awolowo University Teaching Hospital, Ile-Ife between January 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 16 publications
1
31
2
Order By: Relevance
“…This is a relatively high proportion compared with 8.2% found by Adegbehingbe8 in Ile-Ife, Nigeria; 32.5% by Omoti et al .,10 in Benin city, Nigeria; 46.8% by Onyekwe et al .,15 in Onitsha, Nigeria, and 48% by Mafwiri et al .,16 in Tanzania. The high acceptance rate in this study might be related to the verbal consent method of assessing acceptance, and not whether the patient actually returned for surgery.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…This is a relatively high proportion compared with 8.2% found by Adegbehingbe8 in Ile-Ife, Nigeria; 32.5% by Omoti et al .,10 in Benin city, Nigeria; 46.8% by Onyekwe et al .,15 in Onitsha, Nigeria, and 48% by Mafwiri et al .,16 in Tanzania. The high acceptance rate in this study might be related to the verbal consent method of assessing acceptance, and not whether the patient actually returned for surgery.…”
Section: Discussionmentioning
confidence: 67%
“…Despite this recommendation, rates of glaucoma surgery remain low8 in Nigeria. One of the contributing factors is the low rate of acceptance of glaucoma surgery among eligible patients.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a study of 71 eyes of 63 patients showed postoperative IOP of 10–15 mmHg in 82% of cases during follow up period [14]. A study of 46 patients who had the procedure with mean pre-operative IOP of 32.5 ± 6.2 mmHg showed reduction to 14.6 ± 4.2 and 13.5 ± 5.8 mmHg at 3 months and one year, respectively [47]. A study of 100 patients which defined success as IOP less than 22 mmHg or reduction of 30% below preoperative level reported success in 85%, 82%, and 71% at 1, 2, and 5 year postoperative period, respectively [48].…”
Section: Treatment Of Poagmentioning
confidence: 99%
“…An equally low output was observed in a retrospective review in south west Nigeria. 19 Not performing adequate number of glaucoma surgeries, especially in a tertiary teaching institution will have adverse effects on the training of resident doctors. Furthermore, this may create a vicious circle of low output, inadequate skills, poor results, and reduced uptake of glaucoma surgeries.…”
Section: Surgerymentioning
confidence: 99%
“…This is in agreement with the fact that this is the most common glaucoma operation in Africa. 14,19 The use of an antiscarring agent, such as 5FU and mitomycin C (MMC) is beneficial in reducing subconjunctival scarring 21,22 especially in the black population, and MMC has been found to result in lower pressures, 23,24 but the higher cost, higher toxicity, 11,25 low availability, and shorter shelf life are disadvantages. MMC was not used as an adjuvant in any of the centers during this study period.…”
Section: Surgerymentioning
confidence: 99%